LOANS, DEBTS AND INTEREST: A STUDY ON THE RELEVANCE OF DEUT. 23:19-20 FOR CHRISTIANS TODAY - Leal, Jônatas Mattos (Práxis Teológica, 2018)
The relationship of Christians with loans, debts and interest was always a controversial topic. The Old Testament (OT) law dedicates a considerable number of passages to this topic. In a kinsmanship society where survival depended on one another and on the delicate balance between agriculture and production, social justice was a matter of life or death. The text of Deut. 23:19-20 provided directions regarding financial interactions, in the case of one Israelite lending to another fellow citizen or foreigner. Based on the “Progressive Moral Wisdom” method proposed by Roy Gane in his most recent book entitled “Old Testament Law for Christians: original context and enduring application”, the purpose of this paper is to provide a practical application of Deut. 23:19-20 for Christians today. In order to reach this goal, the following discussion will first explore the law itself and its ancient Near East parallels. The second part will analyze the theme of debts and loans from the broad biblical context, particularly regarding the parallel laws of the OT. Then, the third part entitled “The Provisional Divine Solution”, will trace the trajectory of how the concept of loan was developed between the OT and NT. Subsequently, a brief examination on the contrasting treatment of “foreigner” will be undertaken. And finally, the relevance of the law for Christians today will be suggested.